Engineering Metal-Organic Framework-based Nanozymes for Enhanced Biosensing - Xu, Weiqing; Wu, Yu; Jiao, Lei; Gu, Wenling; Du, Dan; Lin, Yuehe; Zhu, Chengzhou (Current Analytical Chemistry, 2022)
Background: Nanozymes are a kind of emerging nanomaterials that can mimic the catalytic activity of natural enzymes with good stability. Objective: Benefited by the unique coordination structure and constitution, metal-organic frameworks (MOFs) have been widely exploited as novel nanozymes. Importantly, various MOFs engineered with fascinating functions provide great opportunities to enhance their enzyme-like activity and improve their applied performance, achieving the goal of vividly mimicking natural enzymes. Conclusion: This review summarized recent advances in the fabrication of the MOFs-based nanozymes and their applications in biosensing. First, MOFs-based nanomaterials containing pristine MOFs, functionalized MOFs, MOFs-based composites and MOFs derivatives are introduced, where the design strategy, enzyme-like activity and the catalytic mechanisms are highlighted systematically. Then, their applications in various target assays are summarized. Finally, the challenges and possible research directions for the development and application of MOFs-based nanozymes are provided.
Keywords: electrochemistry